Analisis Kekuatan Bangunan Rumah Terhadap Banjir Berdasarkan Interpretasi Bentuk Atap Mengunakan Sistem Informasi Geografis Di Desa Kaligayam, Kecamatan Margasari, Kabupaten Tegal - Reosa Andika Firmansyah; Sudibyakto Sudibyakto; Sunarto Sunarto (EnviroScienteae, 2020)
Flood events in Kaligayam Village occur due to rainwater and overflowing rivers trapped in sloping residential areas. Research on the quality of houses in the face of flooding, by grouping based on the shape of the roof, has not been widely carried out, especially in this research area. The use of GIS to analyze the condition of a house in an emergency situation can still be developed to get more detailed results. The population in this study was the house building unit, and the sampling method uses proportional techniques that were randomly selected. The sample of grouping is based on the roof shape of the house that was acquired with Quickbird image interpretation with 0.6 meter spatial resolution. The results of the acquisition of high-rise building data were built with supporting and validated data through field surveys. The database that is processed using GIS to produce data on classes of house buildings in watching flood data on physical conditions, support, and age of the house building. Inventory of all housebuilding parameter data produces a map of the quality of the house building against flooding. In each form of the roof, the building of the house has a variety of different levels of quality in the face of the danger of flooding. The level of quality of the house becomes five levels (very high, high, medium, low, and very low). The type of roof of the village becomes the type of building that has the best quality which is the type of house building with the highest resilience.